Productivity of the Small East African goat and its crosses with the Anglo-Nubian and the Alpine in Rwanda - Wilson, R.T.; Murayi, T. (Springer, 1988)
Examines the productivity of the Small East African Goat and its crosses with the Anglo-Nubian and the Alpine in Rwanda, with particular reference to age at first kidding, kidding interval, litter size, mortality to 150 days, birth weight, total litter weight, and female postpartum weight.